Influencer Marketing and its Role in Creating a Relationship with the Clients of the Y Generation - Stopczyńska , Kinga (Studia Oeconomica Posnaniensia, 2017)
Creating a one-to-one relationship with a customer is a key element of communication. These relations result in access to information about the client - the evolution of needs, expectations, but also ideas, which are an important element of a company's development. The company/brand itself must be attractive not only at the price-quality level, but above all on the field of the creation of experiences and feelings. It is quite complicated when it comes to relations with the Y generation, which is one of the most demanding groups of clients, also considered as one of the most difficult. The aim of the article is to analyse the use of influencer marketing in creating relations with Y generation customers. We focused on the use of the influencer marketing because it has become one of the eagerly used by many companies/brands. The author chose activities oriented around new media with an emphasis on social media: Facebook, and Instagram. This choice is correlated with the interests of the Y generation. The author underlined also the importance of the relations of the third generation as the one that are based on emotions and can influence the customer in the very special way.